PERFORMANCE ANALYSIS FOR THE MOST CONVENIENT WIND TURBINE SELECTION IN WIND ENERGY FACILITY - Zavadskas, Edmundas Kazimieras; Ulutas, Alptekin; Balo, Figen; Stanujkic, Dragisa; Karabasevic, Darjan (Editura Ase, 2022)
As governments seek renewable and more sustainable energy resources, wind energy has emerged as one of the most rapidly developing renewable power resources. The relevance of wind energy turbines has grown as more nations turn to renewable energy. A significant criterion that conduces to wind energy's efficient production is the proper wind turbine's utilize. Due to the fact that a lot of wind turbine manufacturers have built a global presence, it is critical for project administrators to do informed selections about which wind energy turbines to establish in every specific design. Therefore the problem of wind energy turbine choice is critical for nations experiencing global warming and climate change. This study proposes a new hybrid MCDM model including CCSD and MULTIMOOSRAL methods. In this study, 11 100kW wind turbines (T) are evaluated based on 14 criteria. According to the results of the proposed model, T7 coded wind turbine alternative was determined as the best one. The results of the proposed method were compared with other MCDM methods and it was confirmed that the proposed method reached accurate results. In addition, it was determined that the changes in the criteria weights changed the ranking of the alternatives.
Keywords: Renewable Energy; Wind Turbine; CCSD; MULTIMOOSRA